Fabrication and Characterization of Graphene/Epoxy Nanocomposites - Shiuh Chuan HER; Lei Yao CHEN (Medžiagotyra, 2019)
Graphene with high electric and thermal conductivities has been widely used as reinforced filler. In this study, graphene loadings in the range between 0.3 and 1.0 wt.% were added to the epoxy to fabricate the nanocomposites. The mechanical and thermal properties of nanocomposites were characterized using tensile test and differential scanning calorimeter (DSC), respectively. Experimental results show that the elastic modulus, yield strength, ultimate strength and glass transition temperature of the graphene reinforced epoxy are increasing with the increase of the graphene, while the fracture strain and toughness are decreasing with the increase of the graphene. Scanning electron microscope (SEM) was employed to investigate the dispersion and separation of graphene in the epoxy based matrix. The SEM images depict that graphene is well dispersed resulting in a significant improvement of the mechanical and thermal properties of the nanocomposites. The mechanical properties and thermal stability of epoxy nanocomposites with graphenes and multi-walled carbon nanotubes additives were then compared. Experimental results show that nanocomposite with graphene additives outperform the multi-walled carbon nanotube additives.